Program Peningkatan Kesehatan Kerja melalui Edukasi Ergonomi dan Gaya Kerja Sehat pada Pekerja Home Industry - Nita Sofia Rakhmawati; Hasri Widuri; Micko Teguh Tri Cahyo (Politeknik Negeri Cilacap, 2026)
The lanting home industry in Cilacap Regency plays an important role in supporting the local economy. However, the predominantly manual production process places workers at risk of musculoskeletal disorders due to non-ergonomic working postures. This community service program aimed to improve occupational health among lanting workers through ergonomic education and the implementation of healthy work practices. The activity was conducted at one lanting home industry in Cilacap Regency and involved 30 workers. Evaluation was carried out using pre–post tests to assess changes in knowledge levels, complemented by observations of work behavior at the production site. The results showed a significant increase in workers’ knowledge, indicated by an increase in the proportion of workers in the high-knowledge category from 10% before the intervention to 73% after the intervention. Workers began to adopt better working postures, perform light stretching during work breaks, and demonstrated collective awareness by reminding each other to maintain proper working positions. The program proved to be effective, affordable, and easy to implement in improving awareness and healthy work behaviors in small-scale lanting home industries. This activity has the potential to be further developed as a simple ergonomic intervention model for similar traditional food industries.